2016
DOI: 10.1055/s-0036-1593870
|View full text |Cite
|
Sign up to set email alerts
|

The Variable Emergence of the Infrapatellar Branch of the Saphenous Nerve

Abstract: The infrapatellar branch of the saphenous nerve (IPBSN) is a cutaneous nerve of the lower limb, which arises distal to the adductor canal. High variability in the emergence, course, branching, termination, and morphometrics of the IPBSN poses an increased risk of injury to the nerve during surgical interventions on the anteromedial aspect of the knee. The aim of this study was to describe the anatomical characteristics of the IPBSN. This study utilized cadaveric ( = 100) and ultrasonography ( = 30) assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
(59 reference statements)
3
18
0
Order By: Relevance
“…Regardless of the type and length of the incision, the location of the incision also plays an important role in preventing IPBSN iatrogenic injury. In our recent meta‐analysis we found that the horizontal distance between the medial border of the patellar ligament and the IPBSN at the level of the patellar apex, is usually between 45 and 56 mm. Thus, an incision should be performed maximally 45 mm from the medial border of the patellar ligament to minimize the risk of iatrogenic injury to the IPBSN …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Regardless of the type and length of the incision, the location of the incision also plays an important role in preventing IPBSN iatrogenic injury. In our recent meta‐analysis we found that the horizontal distance between the medial border of the patellar ligament and the IPBSN at the level of the patellar apex, is usually between 45 and 56 mm. Thus, an incision should be performed maximally 45 mm from the medial border of the patellar ligament to minimize the risk of iatrogenic injury to the IPBSN …”
Section: Discussionmentioning
confidence: 97%
“…Thus, an incision should be performed maximally 45 mm from the medial border of the patellar ligament to minimize the risk of iatrogenic injury to the IPBSN. 31 This meta-analysis was primarily limited by the variability of the methods used in the included studies. First, most of the studies did not report whether the incision was made based on a reported safe area or angle for autogenous tendon harvesting, such as the one described by Boon et al, 32 or if it was modified according to the size and body mass index of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that this is probably because USG cannot visualize the tiny terminal branches of the IPBSN, injury to which could also lead to postoperative sensory complications. Therefore, we encourage surgeons to remember the safe zones for incision, reported as 3.0 to 4.5 cm from the medial border of the patellar ligament at the level of the apex of the patella (Henry et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the type of emergence of the IPBSN was assessed and classified as: (A) anterior to the on the antero-medial aspect of the knee. SC, subcutaneous tissue; TB, proximal tibia sartorius muscle, (B) posterior to the sartorius muscle, or (C) within (penetrating) the sartorius muscle (Henry et al, 2016). All assessments were performed twice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation